[Rezension von: Roth, Dieter T., 1975-, The Parables in Q] - Howes, Llewellyn 1980-; Roth, Dieter T. 1975- (2020)
On Monday, 19 November 2018, I was fortunate enough to attend a session of the SBL Annual Meeting jointly hosted by the Q Section and the Social Scientific Criticism of the New Testament Section, during which two landmark books on the parables of Jesus were discussed. The first book was The Parables of Jesus the Galilean by Ernest van Eck (see my 2016 review of this book in Acta Theologica 37[1]:135-138), and the second was the current book by Dieter T. Roth. The books were first discussed and reviewed by notable scholars like Paul Foster, Erin Vearncombe and Douglas Oakman, after which Roth and Van Eck deliberated on their own and each other’s works. Apart from being a very stimulating and worthwhile session, during which attention shifted at some stage to the parable of the mustard seed in particular, what stood out clearly at the end was the unmistakable impact of preliminary judgments on the direction and outcome of a study. This is particularly true for contested areas of research like the parables of Jesus and the Sayings Gospel Q, where scholars disagree about issues like the existence and nature of Q, the definition of a parable and the layering of the Jesus tradition. No study demonstrates this more clearly than the monograph by Dieter T. Roth being reviewed here. It is a real strength of the book that presuppositions and preliminary verdicts are explained at the outset.
Keywords: Rezension